Pharmacokinetic, Ambulatory, and Hyperthermic Effects of 3,4-Methylenedioxy-N-Methylcathinone (Methylone) in Rats - Štefková, Kristýna; Židková, Monika; Horsley, Rachel R.; Pinterová, Nikola; Šíchová, Klára; Uttl, Libor; Balíková, Marie; Danda, Hynek; Kuchař, Martin; Páleníček, Tomáš (Frontiers in Psychiatry, 2017)
Methylone (3,4-methylenedioxy-N-methylcathinone) is a synthetic cathinone analogue of the recreational drug ecstasy. Although it is marketed to recreational users as relatively safe, fatalities due to hyperthermia, serotonin syndrome and multi-organ system failure have been reported. Since psychopharmacological data remain scarce we have focused our research on pharmacokinetics, and on a detailed evaluation of temporal effects of methylone and its metabolite nor-methylone on behavior and body temperature in rats. Methylone (5, 10, 20 and 40 mg/kg subcutaneously, s.c.) and nor-methylone (10 mg/kg s.c.) were used in adolescent male Wistar rats across three behavioral/physiological procedures and in two temporal windows from administration (15 and 60 min) in order to test: locomotor effects in the open field, sensorimotor gating in the test of prepulse inhibition (PPI), and effects on rectal temperature in individually and group-housed rats. Serum and brain pharmacokinetics after 10 mg/kg s.c. over 8 h were analysed using liquid chromatography mass-spectrometry (LC-MS). Serum and brain levels of methylone and nor-methylone peaked at 30 min after administration, both drugs readily penetrated the brain with serum : brain ratio 1 : 7.97. Methylone dose-dependently increased overall locomotion. It also decrease the amount of time spent in the center of open field arena in dose 20 mg/kg and additionally this dose induced stereotyped circling around the arena walls. The maximum of effects corresponded to the peak of its brain concentrations. Nor-methylone had approximately the same behavioral potency. Methylone also has weak potency to disturb PPI. Behavioral testing was not performed with 40 mg/kg, because it was surprisingly lethal to some animals. Methylone 10 and 20 mg/kg s.c. induced hyperthermic reaction which was more pronounced in group-housed condition relative to individually-housed rats. To conclude, methylone increased exploration and/or decreased anxiety in the open field arena and with nor-methylone had short duration of action with effects typical for mixed indirect dopamine – serotonin agonists such as 3,4-metyhlenedioxymethamphetamine (MDMA) or amphetamine. Given the fact that the toxicity was even higher than the known for MDMA and that it can cause hyperthermia it possess a threat to users with the risk for serotonin syndrome especially when used in